Toward a framework of ambiguity: a qualitative understanding of healthcare policy design and governance mechanism in China - Qi, Yuanbo; Hu, Aijun; Huang, Panpan (Frontiers in Public Health, 2025)
IntroductionThis study explores the strategic and deliberate usage of ambiguity in Chinese public health policy as a governmental instrument.MethodsBy analyzing 128 official public policy documents and 30 participant interviews as primary evidence, this study developed a three-tier coding instrument to capture the underlying categorizations, strategic functions, and behavioral responses.Results and discussionThe findings of this study indicate that ambiguity, categorized into five types—“Elasticating,” “Generalizing,” “Overloading,” “Substituting,” and “Intensifying”—with “Elasticating” being the most predominant, facilitated the diffusion of accountability, the shifting of responsibility, and the flexibility of interpretation. This research makes a significant contribution to the field of public health governance by redefining policy ambiguity as a complex, integrated mechanism of problem-solving that is rooted in the behavioral, institutional, and bureaucratic contexts of public health operations in China, rather than as a systematic failure.